ACCOUNTING PRACTICE UNDER THE SECURITIES AND EXCHANGE COMMISSION. - Smith, C. Aubrey (The Accounting Review, 1935)
Abstract The Securities Act of 1938, designed to compel full and fair disclosure of material facts relating to securities publicly offered and sold in interstate commerce, has been in operation now some 26 months, during which time approximately 1,700 issues of new securities have been registered with the Federal Trade Commission and its successor, the U.S. Securities and Exchange Commission (SEC). The Securities Exchange Act of 1934, which transferred the administration of the Securities Act from the Federal Trade Commission to the SEC, in addition to continuing the activities of the Federal Trade Commission relative to the Securities Act, is also concerned with the registration of security exchanges, the registration of securities on national security exchanges, and the making of studies and the promulgation of rules relative to certain practices looking toward the public interest and the protection of investors. The public accountant has a direct professional interest in at least one division of this Commission-the registration division. Since the registration requirements covering new issues under the Securities Act and securities listed on national exchanges under the Securities Exchange Act demand financial statements certified by independent public accountants, it is imperative not only that the public accounting profession be kept fully informed as to the statutory requirements as set out under the Commission's rule and regulation.